Pathological Characteristics of Pregnant Tree Shrews Infected by Zoonotic Hepatitis E Virus Genotype and the Effect of Estrogen on Virus Replication - Peiying Zhu; Guojun Wang; Veerasak Punyapornwithaya; Chalita Jainonthee; Jijing Tian; Yan Liu; Fanan Suksawat; Sunpetch Angkititrakul; Yuchen Nan; Zailei Li; Xinhui Duan; Wengui Li (Veterinary Sciences)
Hepatitis E, caused by the hepatitis E virus (HEV), is a zoonotic disease that extends beyond hepatocellular necrosis to replicate in multiple organs. While most infections are self-limiting, HEV infection during pregnancy is associated with severe outcomes, including acute liver failure, preterm delivery, and miscarriage, with the mechanisms underlying this high pathogenicity remaining poorly understood. This study established a pregnant tree shrew model with a late-stage HEV infection and a cellular model using zoonotic HEV genotypes GT3 and GT4 to investigate the effects of estrogen on HEV replication. Results showed that negative-strand RNA detection revealed replicative intermediates in feces and tissues during the acute phase, with peak viral loads occurring within one week and the highest titers in bile. Serum alanine aminotransferase (ALT) and aspartate aminotransferase (AST) levels rose at 3 days post-inoculation (DPI), peaking at 7 DPI. Elevated estrogen levels post-miscarriage correlated with increased viral loads, a trend mirrored in cell culture models showing linear relationships between estrogen and viral replication. Histopathology demonstrated viral hepatitis lesions in liver tissues and abnormalities in the uterus, ovaries, and brain, including hydropic degeneration, neuronal disruption, and granulosa cell necrosis. This study developed a pregnant tree shrew model for HEV infection, providing a robust tool for exploring pathogenic mechanisms during pregnancy and genotype-specific differences in zoonotic HEV pathogenicity. These findings offer new insights into the role of estrogen in HEV replication and its contribution to adverse pregnancy outcomes.